Accuracy of Transvaginal Ultrasonography, Hysteroscopy and Uterine Curettage in Evaluating Endometrial Pathologies - Wanderley, Miriam da Silva; Álvares, Miriam Monteiro; Vogt, Maria de Fátima Brito; Sazaki, Lizandra Moura Paravidine (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Objective To evaluate the accuracy of transvaginal ultrasonography, hysteroscopy and uterine curettage in the diagnosis of endometrial polyp, submucous myoma and endometrial hyperplasia, using as gold standard the histopathological analysis of biopsy samples obtained during hysteroscopy or uterine curettage.Methods Cross-sectional study performed at the Hospital Universitário de Brasília (HUB). Data were obtained from the charts of patients submitted to hysteroscopy or uterine curettage in the period from July 2007 to July 2012.Results One-hundred and ninety-one patients were evaluated, 134 of whom underwent hysteroscopy, and 57, uterine curettage. Hysteroscopy revealed a diagnostic accuracy higher than 90% for all the diseases evaluated, while transvaginal ultrasonography showed an accuracy of 65.9% for polyps, 78.1% for myoma and 63.2% for endometrial hyperplasia. Within the 57 patients submitted to uterine curettage, there was an accuracy of 56% for polyps and 54.6% for endometrial hyperplasia.Conclusion Ideally, after initial investigation with transvaginal ultrasonography, guided biopsy of the lesion should be performed by hysteroscopy, whenever necessary, in order to improve the diagnostic accuracy and subsequent clinical management.
Keywords: endometrial polyp; submucous myoma; endometrial hyperplasia; transvaginal ultrasonography; hysteroscopy; uterine curettage; accuracy